STUDENTS’ PERCEPTION ON TEACHER’S NONVERBAL COMMUNICATION AT SMAN 1 SOPPENG - Andi Erina Faqiha Asnawi; Burhanuddin Arafah (Journal of Innovation Research and Knowledge, 2023)
The study was aimed to explore students’ perceptions of their teacher’s non-verbal communication in teaching English and how nonverbal communications influences students' perception of English teachers' role and performance in the classroom. This study was a descriptive qualitative study conducted at SMAN 1 Soppeng. To achieve the objectives, the data were collected by Likert questionnaire, and interviewing. There were 61 students of eleventh grade in different classes as representative class in school, so the students chosen by purposive cluster sampling technique. The result of this research showed that interpretation to the way teacher’s nonverbal communication affected students’ perception and the way students perceive their teacher’s nonverbal communication is positive. All of the expected meaning behind the nonverbal communication could be understood by the students well. The entire teacher’s nonverbal communication where the researcher focused namely gestures, eye contact, and tone of voice functioned well. Students agreed that the use of nonverbal communication in the teaching and learning process works. Teacher’s nonverbal communication during teaching and learning process made them to be motivated to learn, focused their attention to the teacher’s explanations, and made them eagerly to speak or answer the questions, although there are some students feel nervous, aphetic in learning process, and feel afraid of being noticed.